Dual resonance self-referenced refractive index sensor using 2D silicon photonic crystal cavity waveguide system - Ghosh, Nilaksha; Medhekar, Sarang; Sharma, Puja (Oficyna Wydawnicza Politechniki Wrocławskiej, 2024)
In this work, we have designed and simulated a dual resonance self-referenced refractive index sensor using two dimensional “silicon rods in air” photonic crystal. The proposed sensor uses two wavelengths, namely sensing wavelength and the reference wavelength, to measure the change in the transmission of light with respect to the change in refractive index. It is shown that a change of refractive-index of the photonic crystal rods (in the range of 3.46–3.466) causes a significant change in transmission of the sensing wavelength, while, transmission of the reference wavelength remains almost same. This method of sensing is more efficient in gauging the impact of external factors on the results generated by the sensor. The proposed sensor exhibits a fairly high sensitivity and quality factor of 9912.85%/RIU and 708.17, respectively. The device is compact in size making it portable and hence suitable for field applications. Most of the self-referenced refractive index sensors use wavelength shift to measure different parameters but in the present paper we have used the difference of transmission between two (sensing and reference) wavelengths at a particular refractive-index to calculate the performance of the sensor.
Optica Applicata, Vol. 54, 2024, nr 4, s. 497-509
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; refractive-index sensing; photonic crystal; self-referenced; FDTD; PWE